Strategies for Improving Clean and Healthy Living Behavior in Families: Daily Practices - Azzahra, Feby Indah; Gumilang, Haekhal Ahmad; Hikmal, Muhammad; Virdas, Mohammad; Fadhlulariibah, Naajiah Siti; Muslikah, Siti (Hanifiya: Jurnal Studi Agama-Agama, 2026)
This study aims to explore strategies for improving Clean and Healthy Living Behavior (PHBS) within families as a fundamental effort to enhance community health. PHBS is defined as a set of behaviors practiced consciously to maintain hygiene, health, and disease prevention. The research employed a descriptive approach using observation, interviews, and documentation focusing on families’ daily practices related to PHBS, such as household environmental management, handwashing habits, food handling, and other hygiene practices. The findings reveal that PHBS interventions play a significant role in raising health awareness, reducing the risk of infectious diseases, and strengthening families’ participation in maintaining a healthy environment. Challenges included limited knowledge, low motivation among families, and cultural or habitual barriers that hinder behavioral change. Practical recommendations emphasize the need for continuous health education programs, intensive family mentoring, and government support to integrate PHBS into local health development agendas. This study contributes to the literature by reaffirming the role of families as the primary agents of community health and offering a strategic model of PHBS implementation adaptable to diverse social and cultural contexts.